What Lies behind the "Ambiguity Disadvantages" when Perceiving Dual Images? - Маргарита Г. Филиппова; Наталья В. Андриянова; Роман В. Чернов (Российский психологический журнал, 2023)
Introduction. The focus of the problem of advantages and disadvantages of ambiguity is the question of whether it facilitates or hinders information processing. The relevance of the problem is due to the inconsistency of the available experimental data. Experiments do not take into account whether ambiguity is aware or unaware, but recording it could clarify the problem at hand. Our approach implies separating ambiguity that is both aware and unaware. In our study, we test the idea that the presence of unaware meanings provides greater concreteness of aware meanings compared to unambiguous stimuli. Methods. Stimuli were ambiguous figures. Subjects (n = 92) sorted two sets of cards, each containing one ambiguous figure, into a convenient number of classes. The operationalized hypothesis is that the classes into which images with unaware ambiguity fall will include fewer items than classes without ambiguous figures. Results. Intergroup comparisons revealed the differences expected according to the hypothesis: classes with ambiguous figures were more sparsely populated than classes with unambiguous versions of the same figures. Discussion. Rather than interpreting the result in favor of the disadvantages of ambiguity, we explain it by narrowing the equivalence range of an ambiguity stimulus, allowing the stimulus to be instantiated in an optimal way. The important role of unaware meanings in the process of interpreting perceived information is confirmed.